Lithospheric electrical structure across the Bangong-Nujiang Suture in northern tibet revealed by magnetotelluric - Yang, Zhen; Liang, Hongda; Gao, Rui; Han, Jiangtao; Xin, Zhonghua; Kang, Jianqiang; Shi, Zhuoxuan; Zhang, Lu; Qi, Rui; Li, Huilin (Frontiers in Earth Science, 2023)
Competing hypotheses have been proposed to explain the subduction polarity of the Bangong-Nujiang Tethyan ocean and the formation of the high conductivity anomaly beneath the Qiangtang terrane. However, the lithospheric architecture of the northern Tibetan plateau is still poorly understood due to inhospitable environments and topography. Therefore, in the winter of 2021, a 440 km long, SN-trending broadband magnetotellurics (MT) proﬁle was recorded in northern Tibet in order to detect its regional lithospheric structure. Reliable 2D electrical model was obtained by ablation processing and analysis of broadband MT data to test the lithospheric electrical structure and dynamics between the northern Lhasa and Qiangtang terrane. The inversion result revealed the detailed lithospheric structure of northern Tibet, which synthesizes geological, geochemical and deep seismic reflection evidence, firmly identifies that the trace of south-dipping conductor mainly resulted from the southward subduction of Bangong-Nujiang Tethyan ocean under the Lhasa terrane, and the trace of north-dipping conductor likely due to the northward subduction of Bangong-Nujiang Tethyan ocean under Qiangtang terrane. In addition, the MT proﬁle also images a high-conductivity anticline of lithospheric-scale beneath the central of Qiangtang terrane, which may correspond to the upwelling of post-collisional magmatism triggered by northward subduction of Bangong-Nujiang Tethyan ocean under the southern of Qiangtang terrane, aqueous ﬂuid and/or partial melting.